2013
DOI: 10.4161/auto.25955
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux and oxidative capacity of skeletal muscles during acute starvation

Abstract: Autophagy is an important proteolytic pathway in skeletal muscles. The roles of muscle fiber type composition and oxidative capacity remain unknown in relation to autophagy. The diaphragm (DIA) is a fast-twitch muscle fiber with high oxidative capacity, the tibialis anterior (TA) muscle is a fast-twitch muscle fiber with low oxidative capacity, and the soleus muscle (SOL) is a slow-twitch muscle with high oxidative capacity. We hypothesized that oxidative capacity is a major determinant of autophagy in skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 47 publications
3
55
0
Order By: Relevance
“…An important and novel focus of our study, therefore, was the analysis of skeletal muscle autophagy (9)(10)(11)(12)14,15). First, increased LC3-II and decreased p62 levels indicated that HFD induced autophagy in skeletal muscle (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important and novel focus of our study, therefore, was the analysis of skeletal muscle autophagy (9)(10)(11)(12)14,15). First, increased LC3-II and decreased p62 levels indicated that HFD induced autophagy in skeletal muscle (25).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that adiponectin reduced oxidative stress by downregulating NADPH oxidase by inactivating the phosphorylation of p47 phox , the regulatory subunit of NADPH oxidase (23). Many studies have now established an important crosstalk between oxidative stress and autophagy (24), although the significance in terms in skeletal muscle metabolism (9)(10)(11)(12)14,15) requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to determine autophagic flux 16 by inhibiting the final steps of autophagy using intraperitoneal leupeptin injections. 37,38 In conditions in which mice received leupeptin during the last 2 h of the experiment, starvation did cause LC3B lipidation, both in leukocytes (Fig. 5A, D, G) and hepatocytes ( Fig.…”
Section: Assessment Of Autophagic Markers After Starvationmentioning
confidence: 99%
“…Interestingly, the respiratory muscles of COPD patients show an opposite fibre type shift compared with limb muscles, that is, towards more type I fibres 47, 48. This will have implications for the expression levels of constituents of atrophy signalling pathways 22, 49. Increased catabolic signalling through FOXO and NF‐κB can induce gene expression of key factors in both the ubiquitin proteasome system (UPS)50, 51 and the autophagy lysosome pathway 33, 52…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 99%